Chemical corrosion of metals and alloys - Bore Jegdić; Jovan Popić; Biljana Bobić; Maja Stevanović (Zaštita Materijala)
In this paper, phenomena of chemical corrosion of metals and alloys in electrolyte solutions are analyzed. It is shown that iron, chromium and other metals and alloys dissolve much faster than is the corrosion rate determined by electrochemical methods. This means that the chemical dissolution takes place simultaneously with the electrochemical dissolution. The chemical dissolution does not depend on electrode potential. Under some conditions, chemical dissolution of metals is the dominant process of dissolution. Several mechanisms of chemical corrosion are described. Also, the consequences of chemical dissolution of various metals and alloys are discussed, as well as the hydrogen evolution during the chemical dissolution. The process of hydrogen evolution during the chemical corrosion is not subjected to the laws of electrochemical kinetics.